Investigation of the Supramolecular Assembly of Luminescent Lanthanide Nanoparticles Surface Functionalized by p‐Sulfonato‐Calix[4]arenes with Charged Aromatic Compounds. Issue 36 (28th July 2021) - Cheignon, Clémence; Heurté, Margaux; Knighton, Richard C.; Kassir, Ali A.; Lecointre, Alexandre; Nonat, Aline; Boos, Anne; Christine, Câline; Asfari, Zouhair; Charbonnière, Loïc J.
Abstract: The surface coordination of p ‐sulfonato‐ (C[4]), p ‐sulfonatothia‐ (SC[4]) and p ‐sulfonato‐sulfoxocalix[4]arene (SO2 C[4]) on La0.9 Tb0.1 F3 nanoparticles (TbNP) was investigated by UV‐Vis absorption and luminescence spectroscopies. SO2 C[4] displayed the strongest affinity towards the NPs and a significant antenna effect leading to observation of the characteristic Tb emission bands upon calixarene excitation. NPs decorated by a shell of SO2 C[4] were prepared and the interaction with rhodamine 6G (R6G) was studied. The progressive addition of R6G resulted in a strong Tb to R6G energy transfer process, as revealed by a long lived emission of R6G upon SO2 C[4] excitation. The FRET efficiency was almost quantitative (87–90 %), pointing to an average distance of 28 to 32 Å between the R6G and the Tb emitting centres of the NP. An association of one R6G per SO2 C[4] was deduced with a very strong apparent affinity (K=2.5×10 7  M −1 ) in water. Similar interactions were observed with paraquat, resulting in TbNP luminescence quenching. In both cases, an unexpected increase of the association constant of the cation with SO2 C[4] was observed when SO2 C[4] is anchored at the surface of the NP. Abstract : p‐ Sulfonato‐sulfoxo‐calix[4]arenes were shown to strongly bind to the surface of Tb doped LaF3 nanoparticles, providing an excellent antenna effect for Tb emission. In the presence of some aromatic charged compounds, a strong interaction of the aromatic compounds into the cavity of the surface anchored calixarenes is observed, with a surprising enhancement of the association as compared to the free calixarene in solution.